2010
DOI: 10.1007/s10886-010-9805-3
|View full text |Cite
|
Sign up to set email alerts
|

Host Specific Social Parasites (Psithyrus) Indicate Chemical Recognition System in Bumblebees

Abstract: Semiochemicals influence many aspects of insect behavior, including interactions between parasites and their hosts. We studied the chemical recognition system of bumblebees (Bombus) by examining the cuticular hydrocarbon cues of 14 species, including five species of social parasites, known as cuckoo bees (subgenus Psithyrus). We found that bumblebees possess species-specific alkene positional isomer profiles that are stable over large geographical regions and are mimicked by three host-specific cuckoo parasite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
66
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 43 publications
1
66
0
Order By: Relevance
“…Van Wilgenburg et al [5] suggested that this pattern indicates a gradual mode of evolution for alkenes in ants and no essential role of them in the discrimination of closely related species [4,5], but see Martin & Drijfhout [23] who found no correlation between cuticular hydrocarbons and phylogeny in ants. In bumblebees, chemical distances of alkenes also closely match phylogenetic distances (T. Schmitt, C. Jarvers, S. Leonhardt, personal observation), whereas the composition of n-alkanes is relatively stable across species [24], further pointing to potentially different functions of these two compound groups. The entire bouquet of Dufour's gland secretions (used for nest cell linings) in turn nicely matches the phylogenies in Colletidae, Halictidae, Oxaeidae and Andrenidae [28,63], indicating a uniform function of all components within Dufour's glands.…”
Section: (I) Resin-derived Compoundsmentioning
confidence: 86%
“…Van Wilgenburg et al [5] suggested that this pattern indicates a gradual mode of evolution for alkenes in ants and no essential role of them in the discrimination of closely related species [4,5], but see Martin & Drijfhout [23] who found no correlation between cuticular hydrocarbons and phylogeny in ants. In bumblebees, chemical distances of alkenes also closely match phylogenetic distances (T. Schmitt, C. Jarvers, S. Leonhardt, personal observation), whereas the composition of n-alkanes is relatively stable across species [24], further pointing to potentially different functions of these two compound groups. The entire bouquet of Dufour's gland secretions (used for nest cell linings) in turn nicely matches the phylogenies in Colletidae, Halictidae, Oxaeidae and Andrenidae [28,63], indicating a uniform function of all components within Dufour's glands.…”
Section: (I) Resin-derived Compoundsmentioning
confidence: 86%
“…Linear alkanes are primarily anti-desiccation agents (Howard and Blomquist, 2005;Gibbs and Rajpurohit, 2010), whereas branched alkanes are reputed to serve as recognition cues (Dani et al, 2001(Dani et al, , 2005Châline et al, 2005;Martin et al, 2008;. The role of alkenes is less clear, but they are found in the profiles of parasitic ants and bumblebees (Bonavita-Cougourdan et al, 2004;Lambardi et al, 2007;Martin et al, 2010) and are repellents in some cases, as in bees (Dani et al, 2003). In this light, it is not surprising that velvet ants and pre-invasion social parasites (that gain from being undetectable and limiting host contacts) are poor in branched alkanes and rich in potentially repellent alkenes.…”
Section: Discussionmentioning
confidence: 99%
“…Error bars are standard errors alkene and fatty acid isomers may contain sufficient variation to separate colonies. A recent study (Martin et al, 2010) found that bumblebees have a high diversity of alkene isomers, of which some are mimicked by bumblebee parasites, thereby enabling them to integrate into the host colony. Furthermore, newly emerged bees are readily accepted into colonies if they lack essential nestmate recognition compounds; this is known as the Blank Slate Theory proposed by Breed et al (2004).…”
Section: Discussionmentioning
confidence: 99%